Emotional Intelligence and Its Psychological Determinants: An Integrative Review - Inayat Ul Haq; Dr. Jawad Haseeb (Journal of Religion and Society, 2026)
Emotional intelligence (EI) is a pivotal psychological construct linked to academic achievement, adaptive functioning, and psychosocial well-being. Despite extensive research on EI, limited attention has been devoted to a systematic examination of its underlying determinants within undergraduate populations in developing contexts. This article investigates the key psychological factors influencing emotional intelligence among undergraduate students enrolled in universities in Wah Cantt, Pakistan. Grounded in established frameworks of emotional, biological, and developmental psychology, the study examines biological and neurological predispositions, developmental influences including parenting styles and childhood experiences, the educational ecosystem, and socio-demographic characteristics such as gender, age, and socio-economic status. Derived from the theoretical foundation of a doctoral dissertation, the study adopts a descriptive and integrative analytical approach supported by relevant empirical literature. The findings underscore the multidimensional nature of emotional intelligence, demonstrating that EI emerges from the dynamic interaction between innate capacities and environmental conditions, with developmental and educational contexts exerting particularly strong influence during early adulthood. The study contributes to the psychological literature by offering a comprehensive synthesis of EI determinants and provides evidence-based insights for higher education institutions seeking to promote emotional competence and holistic student development. Keywords: Emotional Intelligence, Psychological Determinants, Developmental Factors, Educational Environment, Socio-Demographic Influences